Tunable AI-CPL behavior by regulation of microstructure of AIE-active isomers through chiral emissive liquid crystals. (February 2021) - Li, Yang; Shen, Yihao; Liu, Kerui; Quan, Yiwu; Cheng, Yixiang
Abstract: Circularly polarized luminescence (CPL) emission materials with high luminescence dissymmetry factor ( g lum ) and high quantum yield (QY) are currently in urgent demand for real applications. Three D-A type enantiomers ( R-/S- 1, 2 and 3) were designed and synthesized that combine a phenanthro [9, 10- d ]imidazole (PIP) unit to a naphthalimide (NI) at the p-, m-, o- positions. These AIE-active enantiomers were chosen as CPL emitters doped into nematic liquid crystals (E7, N-LCs) to form three chiral nematic liquid crystals (N*-LCs-1, 2 and 3). Interestingly, N*-LCs-1 shows higher g lum (+0.91/-0.98) and QY (18.5%) than N*-LCs-2 ( g lum = +0.86/-0.89, QY = 1.3%) and N*-LCs-3 ( g lum = +0.010/-0.013, QY = 4.7%) due to effective chirality transfer and intramolecular electronic coupling from microstructure change of AIE-active isomers. This paper revealed that AI-CD and AI-CPL enhancement behavior of N*-LCs could be regulated not only by the chirality transfer via supramolecular self-assembly but also by the electronic coupling strength through microstructure change of AIE-active isomers of donor units in the chiral emitters. This work can provide a new strategy for the development of CPL LCs materials. Graphical abstract: Image 1 Highlights: Three AIE-active enantiomers were doped into E7 to form chiral nematic liquid crystals and emit the amplified CPL signals. The AI-CPL behavior can be regulated by the chirality transfer and electronic coupling strength of chiral emitters. R-/S- 1 with donor unit at para- position can exhibit stronger AI-CPL behavior in N*-LCs.